Pharmaceutical manufacturing encyclopedia. - Sittig, Marshall (William Andrew Pub., 2007)
Annotation This industry standard encyclopedia on pharmaceutical manufacturing processes has been completely updated to include FDA drugs approved up to the summer of 2004. The encyclopedia gives details for the manufacture of 2226 pharmaceuticals that are being marketed as a trade-named product somewhere in the world. Each entry includes: ò Therapeutic function ò Chemical and common name ò Structural Formula ò Chemical Abstracts Registry no. ò Trade name, manufacturer, country, and year introduced ò Raw Materials ò Manufacturing Process In addition, references are also cited under each drug's entry to major pharmaceutical works where additional information can be obtained on synthesis and the pharmacology of the individual products.
Revised edition of: Pharmaceutical manufacturing encyclopedia / by Marshall Sittig. ©1988.
Keywords: Drugs -- Synthesis -- Dictionaries.; Pharmaceutical chemistry -- Dictionaries.; Drugs.; Pharmaceutical chemistry.; elektronické knihy; electronic books